THE MOST EFFECTIVE ENGLISH TEACHING METHODS IN RURAL SCHOOLS - Darius Yonatan Nama; Christmas Prasetia Ate (Jurnal As-Salam, 2022)
Effective teaching methods in many contexts are still a concern when it comes to teaching English as a foreign language in Indonesia. It relates to a lack of English proficiency. Even after six years of formal language learning, students can still not acquire productive English abilities such as speaking and writing. This study's main objective is to find the English teachers' perspectives concerning the most effective teaching methods in rural schools throughout four districts, Malaka, Kupang, Timor Tengah Utara, and Timor Tengah Selatan. The mixed-method was administered through a questionnaire, data collected from 26 English teachers at Senior High School who met the criteria. In addition, eight respondents were interviewed to learn how to apply effective methods. The most effective methods of teaching English in rural areas include Suggestopedia, Audio-Lingual Method, Communicative Language Teaching, and Task-Based Language Teaching.